PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWANPADA PT KARYA MULTI SOLUSI BUMI SERPONG DAMAI TANGERANG SELATAN - Sumiaty, Raden Yeti; Cay, Sam (RJABM (Research Journal of Accounting and Business Management), 2024)
This research aims to examine the influence of motivation and work environment on the performance of employees of PT Karya Multi Solusi BSD South Tangerang. The data used in this research is primary data by distributing questionnaires to employees of PT Karya Multi Solusi BSD South Tangerang. This research uses a quantitative approach using survey methods. The sampling method used was non-probability sampling, with the sampling technique using purposive sampling. The sample in this study was 100 employees of the production division of PT Karya Multi Solusi BSD South Tangerang. The data analysis method used is multiple regression analysis. The results of this research prove that motivation has a positive and significant effect on the performance of PT Karya Multi Solusi BSD South Tangerang employees, the work environment has a positive and significant effect on the performance of PT Karya Multi Solusi BSD South Tangerang employees.